Anesthesia management in cesarean section with severe preeclampsia and non-reactive nonstress test - Manuaba, Ida Bagus Gede Raden Shuwawhibawa; Widana, I. Wayan (International Journal of Research in Medical Sciences, 2024)
Maternal death and morbidity remain a global health issue. It is noted that 15%-20% of maternal deaths are due to complications of hypertension in pregnancy, namely preeclampsia. In cases of preeclampsia requiring cesarean section, anesthesia is necessary. A 23-year-old pregnant woman presented with complaints of decreased fetal movement for the past 2 days. She also reported headache and decreased vision. Physical examination revealed increased blood pressure (160/110 mmHg) and +1 protein in urine. Nonstress test showed non-reactive results. The patient was diagnosed with severe preeclampsia at 37 weeks 1 day gestation and underwent an urgent cesarean section. Anesthesia was managed using a subarachnoid block with bupivacaine 0.5% 12.5 mg, resulting in total block. The operation lasted 1 hour, and a baby boy was delivered with a weight of 1950 gm, length 50 cm, and APGAR score 7-8-9. Anesthetic management in preeclampsia cases must prioritize the safety of both mother and baby. Each anesthesia technique has its advantages and disadvantages.